Peripheral Arterial Aneurysms (Firat Experience) - Uysal, Ayhan; Burma, Oktay (Fırat University, 2007)
Objective: Peripheral arterial aneurysms are frequently encountered due to increased incidence of arteriosclerosis and common use of invasive methods for diagnostic and therapeutic purposes. The aim of this report is to retrospectively evaluate preoperative features of peripheral arterial aneurism cases operated at our clinic and their results of surgical treatment. Materials and Methods: A total of 23 peripheral arterial aneurysm cases diagnosed and operated at our clinic between the years of 1994 and 2004 were retrospectively evaluated. Results: Acute and chronic ischemias of extremities were determined in 12 cases (52.1%). True aneurysm and pseudo-aneurysm were seen in 12 (52.2%; more than one aneurysms in three cases) and 11 (47.8%) cases. In etiology, most frequent causes for true and pseudo-aneurysms were recorded to be arteriosclerosis and iatrogenic factors, respectively. Most frequent localization of 26 aneurysms was in the femoral and popliteal arteries. It was noted that aneurysmectomy combined with interposition of sapheneous vein or synthetic graftl was the most commonly applied surgical method. Conclusions: In a total of three cases (13%) amputation (two lower extremity toes and 1 upper-knee) was performed. One patient deceased as a result of post-operative pulmonary edema. It is suggested that peripheral aneurysms (even asymptomatic cases) must be surgically treated since they may cause complications and reduce the success rate of operations to be performed. ©2007, Firat University, Medical Faculty

Amaç: Periferik arter anevrizmalarına gerek arteriyoskleroz insidansında artış, gerekse tanı ve tedavi amaçlı invaziv metodların yaygın kullanımı nedeniyle sıklıkla rastlanılmaktadır. Bu çalışmamızın amacı kliniğimizde periferik arter anevrizması nedeniyle opere edilen olguların preoperatif özelliklerini, cerrahi tedavi sonuçlarını retrospektif olarak değerlendirmektir. Gereç ve Yöntem: Kliniğimizde 1994-2004 yılları arasında periferik arter anevrizma saptanan 23 olgu retrospektif olarak incelendi. Bulgular: Akut ve kronik olmak üzere toplam 12 (%52.1) olguda ekstremite iskemisi mevcuttu. Gerçek anevrizma 12 (%52.2) (3 olguda birden fazla anevrizma), psödo-anevrizma ise 11 (%47.8) olguda tesbit edildi. Etiyolojide gerçek anevrizmalarda en sık olarak arteriyoskleroz, psödoanevrizmalarda ise iyatrojenik nedenler saptandı. Toplam 26 anevrizmanın en sık yerleşim bölgeleri femoral ve popliteal arterler olup en sık uygulanan cerrahi yöntemin anevrizmektomi ile birlikte safen ven veya vasküler greft ile interpozisyon olduğu saptandı. Sonuç: Toplam 3 (%13) olguda amputasyon (2 alt ekstremite parmak ve 1 diz üstü) gerekti. Bir hastamız ise postoperatif akciğer ödemi sonucu kaybedildi. Komplikasyon gelişimi, yapılacak müdahalelerin başarı şansını azaltacağı için asemptomatik bile olsa periferik anevrizmalar mutlaka cerrahi olarak tedavi edilmelidir kanaatindeyiz. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Periferik Arter Anevrizmaları (Fırat Deneyimi)